Antibiofilm properties of lactic acid bacteria and their metabolites against Salmonella enterica serotype Enteritidis on eggshell surface - Lina E. Merino; Mariángeles Noto Llana; Ailín Garófalo; Fernando M. Trejo; Marina A. Golowczyc (Current Research in Microbial Sciences)
Salmonella enteritidis (SE) is a pathogenic bacterium commonly found on the surface of eggshells. In this study, we investigated the biofilm formation of a specific strain of S. enteritidis, CIDCA 115 (SE 115) on eggshells. Additionally, we examined the impact of Lentilactobacillus kefiri strains 83113 and 8321, as well as Lactiplantibacillus plantarum 83114, and their metabolites present in the supernatant on the biofilm formation of SE 115. Scanning electron microscopy revealed that SE 115 formed a mature biofilm structure on the eggshell. During co-incubation and pre-incubation, lactic acid bacteria strains significantly reduced the formation of SE 115 biofilm (p < 0.05 and p < 0.01, respectively) compared to SE 115 grown alone. The cell-free supernatants of lactic acid bacteria also exhibited a reduction in SE 115 biofilm formation and modified its structure. Co-incubation with SE 115 induced alterations in the composition of biofilm matrix components, notably in the levels of fimbria curli and cellulose. The qPCR analysis revealed that, after 48 h of incubation, the expression of the csgD gene, a critical regulator of biofilm formation, remained unchanged compared to planktonic cells. However, genes associated with the production of biofilm matrix components, curli (csgA) and cellulose (bcsA), exhibited heightened expression in the presence of lactic acid bacteria compared to the planktonic state. This study highlights the potential of lactic acid bacteria strains and their metabolites as innovative strategies for managing Salmonella biofilm formation in the context of poultry production.